Synthesis, Spectroscopic Characterization and Preliminary Antimicrobial Studies of Mn(II) and Cu(II) Complexes of two Thiolates; S,S’-(2,6-Diaminopyridine-3,5-diyl) Dibenzenecarbothioate (DBCT) and S-Benzyl Benzenecarbothioate (BBCT) - P. O. Ukoha; C.U. Alioke; N.L> Obasi; K.F. Chah (E-Journal of Chemistry)
S,S’-(2,6-Diaminopyridine-3,5-diyl)dibenzenecarbothioate was formed by condensing 2,6-diamino-3,5-dithiopyridine and benzoyl chloride in the presence of pyridine. Also S-benzyl benzenecarbothioate was prepared by the condensation of benzoyl chloride and phenylmethanethiol in the presence of pyridine. The complexes of these compounds were prepared using copper(II) and manganese(II) chloride salts. The thiolates were characterized on the basis of their electronic, infrared and NMR spectra whereas the complexes were characterized via electronic and infrared studies. The IR spectral studies indicate that the ligands coordinated through the carbonyl oxygen, the sulphur atom and also with the amino group in DBCT. Antimicrobial studies on the ligands and their complexes showed varying degrees of inhibition on the growth of the following microorganisms; Staphylococcus aureus (ATCC 25923), Pseudomonas aeruginosa (ATCC 27853), Bacillus subtilis (ATCC 6633) and Candida albicans (ATCC 2091). The compounds showed no activity against Escherichia coli (ATCC 25922)